First year nursing students' experiences of social media during the transition to university: a focus group study. Issue 5 (29th August 2016) - Ferguson, Caleb; DiGiacomo, Michelle; Saliba, Bernard; Green, Janet; Moorley, Calvin; Wyllie, Aileen; Jackson, Debra
Abstract : Background: Social media platforms are useful for creating communities, which can then be utilised as a mean for supportive, professional and social learning. Objective : To explore first year nursing student experiences with social media in supporting student transition and engagement into higher education. Design : Qualitative focus groups. Methods : Ten 1st year Bachelor of Nursing students were included in three face-to-face focus groups. Data were analysed using qualitative thematic content analysis. Results : Three key themes emerged that illustrates the experiences of transition and engagement of first year student nurses using social media at university. (1) Facilitating familiarity and collaboration at a safe distance, (2) promoting independent learning by facilitating access to resources, and (3) mitigating hazards of social media. Conclusion : This study has demonstrated the importance of social media in supporting informal peer–peer learning and support, augmenting online and offline relationships, and building professional identity as a nurse.